2022
DOI: 10.1111/ppl.13623
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide structural and functional features of single nucleotide polymorphisms revealed from the whole genome resequencing of 179 accessions of Arachis

Abstract: Peanut being an important food, oilseed and fodder crop worldwide, its genetic improvement currently relies on genomics-assisted breeding (GAB). Since the level of marker polymorphism is limited in peanut, the availability of a large number of DNA markers is the prerequisite for GAB. Therefore, we detected 4,309,724 single nucleotide polymorphisms (SNPs) from the whole genome re-sequencing (WGRS) data of 178 peanut accessions along with the reference genome sequence of Tifrunner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These variants can be all used in molecular marker-assisted breeding. But the number of SNPs in Monticola and Pingdu9616 was significantly less than the studies conducted by Bhat et al [30] which indicated that wild and the cultivated species are obviously different in genotype. Compared with other studies in gene family, most gene family such as TFs from 57 families and GeBP family were identified less in Monticola and Pingdu9616 than Fuhuasheng [15].…”
Section: Discussionmentioning
confidence: 59%
“…These variants can be all used in molecular marker-assisted breeding. But the number of SNPs in Monticola and Pingdu9616 was significantly less than the studies conducted by Bhat et al [30] which indicated that wild and the cultivated species are obviously different in genotype. Compared with other studies in gene family, most gene family such as TFs from 57 families and GeBP family were identified less in Monticola and Pingdu9616 than Fuhuasheng [15].…”
Section: Discussionmentioning
confidence: 59%
“…Arahy.W1P0U6 and Araip.SJ8UT genes though code for disease resistance proteins, previous reports showed their induction under drought stress in peanut (Khan et al 2020;Deng et al 2018) and maize (Yang et al 2021). The SNP at Ah02_1558700 was found to be rare since it was detected only between TMV 2 and TMV 2-NLM but not among any of the 179 accessions of peanut (Bhat et al 2022). Other two genes, Arahy.H3LZVP and Arahy.23PCL8 in the same QTL region code for mediator of RNA polymerase protein and protein kinase super-family protein, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Such improvements have facilitated the rapid sequencing of the whole genomes of a large number of plant species, leading to the identification and characterization of new and important genes, alleles, and molecular markers. Bhat et al (2022) used the whole-genome resequencing (WGRS) data obtained from 178 peanut genotypes to identify more than 4.3 million SNPs. Of these, 2488 SNPs had a high impact due to the gain of stop codons, variations in splice acceptors and splice donors, and the loss of start codons.…”
mentioning
confidence: 99%